Mal de Río Cuarto virus infection causes hormone imbalance and sugar accumulation in wheat leaves - De Haro, Luis Alejandro; Arellano, Sofía Maité; Novak, Ondrej; Feil, Regina; Dumon, Analia Delfina; Mattio, Maria Fernanda; Tarkowska, Danuse; Llauger, Gabriela; Strnad, Miroslav; Lunn, John Edward; Pearce, Stephen; Figueroa, Carlos María; et al. (BMC, 2019)
Background; Mal de Río Cuarto virus (MRCV) infects several monocotyledonous species including maize and wheat. Infected plants show shortened internodes, partial sterility, increased tillering and reduced root length. To better understand the molecular basis of the plant-virus interactions leading to these symptoms, we combined RNA sequencing with metabolite and hormone measurements. Results: More than 3000 differentially accumulated transcripts (DATs) were detected in MRCV-infected wheat plants at 21 days post inoculation compared to mock-inoculated plants. Infected plants exhibited decreased levels of TaSWEET13 transcripts, which are involved in sucrose phloem loading. Soluble sugars, starch, trehalose 6-phosphate (Tre6P), and organic and amino acids were all higher in MRCV-infected plants. In addition, several transcripts related to plant hormone metabolism, transport and signalling were increased upon MRCV infection. Transcripts coding for GA20ox, D14, MAX2 and SMAX1-like proteins involved in gibberellin biosynthesis and strigolactone signalling, were reduced. Transcripts involved in jasmonic acid, ethylene and brassinosteroid biosynthesis, perception and signalling and in auxin transport were also altered. Hormone measurements showed that jasmonic acid, brassinosteroids, abscisic acid and indole-3-acetic acid were significantly higher in infected leaves. Conclusions: Our results indicate that MRCV causes a profound hormonal imbalance that, together with alterations in sugar partitioning, could account for the symptoms observed in MRCV-infected plants.